PENGARUH EPS (EARNING PER SHARE), PER (PRICE EARNING RATIO), NPM (NET PROFIT MARGIN), DAN FINANCIAL DISTRESS TERHADAP HARGA SAHAM - Melia Ayu Lestari; Anastasia Anggarkusuma Arofah; Karunia Zuraidaning Tyas (Perwira Journal of Economics & Business, 2026)
This study aims to empirically test the effect of EPS (Earning Per Share), PER (Price Earning Ratio), NPM (Net Profit Margin), and Financial Distress on stock prices. The type of research used is quantitative. The population of this study was 31 trading companies in the retail trade subsector listed on the Indonesia Stock Exchange in 2020-2023, while the sample of this study was 12 companies selected using a purposive sampling technique, so that the total sample that can be used for 4 years is 48 samples. The type of data used is secondary data. The data collection techniques used were literature study and documentation study. The data analysis technique used multiple linear regression analysis with the help of the SPSS application version 25. The results of this study indicate that EPS has a partial positive effect on stock prices, PER has a positive effect on stock prices, NPM has no effect on stock prices, and Financial Distress has no effect on stock prices.